Basic English Book 3 - Kaur, Harbans (University Press Plc, 2003)
This book is an essential and helpful guide to every student for acquiring competence in the English language. It contains useful reference materials for enrichment of vocabulary and general knowledge as well as a section on language use and grammar$1! =s
Keywords: Juvenile Non-Fiction / Language-English